2017
DOI: 10.54386/jam.v19i2.686
|View full text |Cite
|
Sign up to set email alerts
|

Crop weather relationship in preseasonal sugarcane (Var. CoM 0265)

Abstract: A field experiment was carried out at Central Sugarcane Research Station Padegaon, during 2011-12 to 2013-14 to assess the crop weather relationship in preseasonal sugarcane (var. CoM 0265). Treatments were comprised of nine planting dates at 15 days interval starting from 15th October to 15th February. The results indicated that the early planting produced highest cane and CCS (commercialcane sugar) yield. Significantly the highest brix (21.3), sucrose (20.4%), purity (96.8%) and CCS (14.6%) were observed und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The previously mentioned statement suggests that these problems can be effectively addressed through the adoption of bud-chip technology for sugarcane planting to avoid the inconveniences associated with conventional planting methods. Many workers proved the negative influence of decreasing the length of growing season on sugarcane yield, among them Kamel (2020) and Chaudhari et al (2017). Also, Galal et al (2015) reported that growing sugarcane using seedlings transplanted to the field in April did not result in any reduction in cane yield and allowed the harvesting of broad bean winter crop intercropped with sugarcane, compared to the conventional planting of sugarcane using cane setts.…”
Section: Introductionmentioning
confidence: 99%
“…The previously mentioned statement suggests that these problems can be effectively addressed through the adoption of bud-chip technology for sugarcane planting to avoid the inconveniences associated with conventional planting methods. Many workers proved the negative influence of decreasing the length of growing season on sugarcane yield, among them Kamel (2020) and Chaudhari et al (2017). Also, Galal et al (2015) reported that growing sugarcane using seedlings transplanted to the field in April did not result in any reduction in cane yield and allowed the harvesting of broad bean winter crop intercropped with sugarcane, compared to the conventional planting of sugarcane using cane setts.…”
Section: Introductionmentioning
confidence: 99%